Lewis Acid Catalyzed Cycloaddition of Bicyclobutanes with Ynamides for the Synthesis of Polysubstituted 2‐Amino‐bicyclo[2.1.1]hexenes - Hu, Qian‐Qian; Wang, Liu‐Yang; Chen, Xing‐Hao; Geng, Ze‐Xiang; Chen, Jie; Zhou, Ling (Angewandte Chemie International Edition, 2024)
Synthesis of bicyclic scaffolds has gained significant attention in drug discovery due to their potential to mimic benzene bioisosteres. Here, we present a mild and scalable Sc(OTf)3‐catalyzed [3+2] cycloaddition of bicyclo[1.1.0]butanes (BCBs) with ynamides, yielding a diverse array of polysubstituted 2‐amino‐bicyclo[2.1.1]hexenes in good to excellent yields. These products offer valuable starting materials for the construction of novel functionalized bicyclo[1.1.0]butanes. Preliminary mechanistic studies indicate that the reaction involves a nucleophilic addition of ynamides to bicyclo[1.1.0]butanes, followed by an intramolecular cyclization of in situ generated enolate and keteniminium ion. We expect that these findings will encourage utilization of complex bioisosteres and foster further investigation into BCB‐based cycloaddition chemistry. A Sc(OTf)3‐catalyzed cycloaddition of bicyclo[1.1.0]butanes with ynamides was developed, enabling access to a variety of polysubstituted 2‐amino‐bicyclo[2.1.1]hexenes in good to excellent yields. The prepared products serve as valuable precursors for the synthesis of novel and functionally diverse bicyclo[1.1.0]butanes, showcasing their potential utility in other fields.